Achieving Food System Resilience Requires Challenging Dominant Land Property Regimes - Calo, Adam; McKee, Annie; Perrin, Coline; Gasselin, Pierre; McGreevy, Steven; Sippel, Sarah Ruth; Desmarais, Annette Aurélie; Shields, Kirsteen; Baysse-Lainé, Adrien; Magnan, André; Beingessner, Naomi; Kobayashi, Mai (Frontiers in Sustainable Food Systems, 2021)
Although evidence continues to indicate an urgent need to transition food systems away from industrialized monocultures and toward agroecological production, there is little sign of significant policy commitment toward food system transformation in global North geographies. The authors, a consortium of researchers studying the land-food nexus in global North geographies, argue that a key lock-in explaining the lack of reform arises from how most food system interventions work through dominant logics of property to achieve their goals of agroecological production. Doing so fails to recognize how land tenure systems, codified by law and performed by society, construct agricultural land use outcomes. In this perspective, the authors argue that achieving food system “resilience” requires urgent attention to the underlying property norms that drive land access regimes, especially where norms of property appear hegemonic. This paper first reviews research from political ecology, critical property law, and human geography to show how entrenched property relations in the global North frustrate the advancement of alternative models like food sovereignty and agroecology, and work to mediate acceptable forms of “sustainable agriculture.” Drawing on emerging cases of land tenure reform from the authors' collective experience working in Scotland, France, Australia, Canada, and Japan, we next observe how contesting dominant logics of property creates space to forge deep and equitable food system transformation. Equally, these cases demonstrate how powerful actors in the food system attempt to leverage legal and cultural norms of property to legitimize their control over the resources that drive agricultural production. Our formulation suggests that visions for food system “resilience” must embrace the reform of property relations as much as it does diversified farming practices. This work calls for a joint cultural and legal reimagination of our relation to land in places where property functions as an epistemic and apex entitlement.